C-MORE brain MRI database - Griffanti, L; Raman, B; Alfaro-Almagro, F; Filippini, N; Cassar, M; Sheerin, F; Okell, T; Kennedy McConnell, F; Chappell, M; Wang, C; Arthofer, C; Lange, F; et al. (University of Oxford, 2021)
Please refer to readme.txt file